The effect of layout placement on acoustic conditions in call centers: Evaluations within the scope of an example - Gurturk, Semran Ozdem; Akdag, Nese Yugruk (Sage Publications Inc, 2024)
This article aimed to provide auditory comfort conditions in call centers where the noise problem is very high and its use is increasing day by day. Since there are no partition walls in such places, noises from conversations, telephones and other office equipment, footsteps, air conditioning and lighting, office equipment (fax machines, printers, etc.), and noise from outside can reduce working efficiency and sometimes cause serious health problems. To assess this situation, the current noise levels situation in a call center were revealed with the help of observation, survey, measurement, and simulation. The number of personnel in the volume, different layout models, surface absorption, and obstacle heights were analyzed through the simulation program and appropriate call center models were obtained in terms of acoustic comfort. By taking the models as a reference, noise level maps have been prepared according to different frequency spectrums. When the noise maps are evaluated, while the call center noise level is 60 dBA in the current situation, it has decreased to 45-53 dBA noise levels as a result of the settlement proposal where the employees are facing in opposite directions in pairs. There has been a reduction in noise level of approximately 16%. As a result of the study, the measures to be taken to improve the auditory environment were determined within the scope of architectural and acoustic design, and results were obtained to guide the designers.
Keywords: Call center; acoustic comfort; acoustic design parameters